Cubic liquid crystalline nanoparticles (cubosomes) to improve solubility and bioavailability of poorly water soluble drugs: A review - ThadiVineetha; I. Bala Tripura Sundari; M. Bhagawan Raju (International Journal of Pharmacy and Analytical Research, 2022)
The advances in lipid-based drug carriers have gained a greater significance in the field of drug delivery systems. There are several kinds of lipidic carriers, including emulsions, Liposomes, solid lipid nanoparticles, cubosomes, and micelles. Recently the use of monoolein based cubosomes for the delivery of drug have attracted much of the scientists due to their bioadhesion, sustained release of incorporated drugs, protecting drugs from physical and enzymatic degradation, nontoxic nature of structure-forming materials of cubosomes and solubilization of hydrophilic, amphiphilic and lipophilic drugs. Cubosomes are liquid crystalline nanostructures formed from the cubic phase of lipids, such as monooleate, or any other amphiphilic macromolecules with the unique property to be dispersed into particles. The present review gives an overview of cubosomes that includes structure, materials, and methods of preparation and their characterization.